N-terminal pro-B-type natriuretic peptide as a predictive marker of the outcomes of fibrinolytic therapy in acute ST-elevation myocardial infarction - Amit Kumar; Shweta Tanwar; Rajesh Chetiwal (MGM Journal of Medical Sciences)
Background: Risk assessment is vital in delivering appropriate treatment and enhancing patient outcomes during acute ST-elevation myocardial infarction (STEMI). This study sought to ascertain the significance of NT-proBNP in predicting the outcome of thrombolysis in acute STEMI. Materials and Methods: In this prospective study, we enrolled individuals with acute STEMI who underwent fibrinolytic therapy. Plasma N-terminal-proBNP (NT-proBNP) levels were assessed upon admission. Patients were categorized as thrombolysis success or failure groups based on electrocardiogram (ECG) criteria. The outcomes were measured in terms of in-hospital mortality and adverse cardiovascular events. Results: Thrombolysis achieved success in 59.13% of acute STEMI cases. Patients experiencing failed thrombolysis had a significantly longer mean time to reperfusion than those with successful thrombolysis (4.74 ± 2.42 vs. 5.97 ± 2.35 h, P = 0.0078). The median baseline NT-proBNP concentration was 983 pg/mL (interquartile range 777–2987 pg/mL). The plasma NT-proBNP levels on admission were notably higher in the thrombolysis failure group (P < 0.001). NT-proBNP, time to reperfusion, heart rate, blood urea, and serum uric acid exhibited negative correlations with thrombolysis outcomes. The most prevalent adverse event was cardiac failure. Receiver operating characteristic (ROC) curve analysis indicated a robust association between NT-proBNP and in-hospital mortality. High NT-proBNP (>983 pg/mL) and prolonged time to reperfusion (>6 h) emerged as independent predictors of thrombolysis failure on multivariate logistic regression analysis (P = 0.017 and 0.035, respectively). Conclusion: Elevated plasma NT-proBNP upon admission during acute STEMI serves as a robust predictor for both fibrinolytic therapy failure and in-hospital mortality.